The effectiveness of gamification-based platforms in developing psychological hardiness among students with high levels of psychological disorders - Alharthi, Majed Abdallah (Edelweiss Applied Science and Technology, 2026)
Many diverse educational situations present various challenges, which must be considered to find suitable solutions. Gamification-based platforms have significantly contributed to enhancing learning by employing various motivational elements that greatly contribute to developing intrinsic motivation. This study focused on examining the effectiveness of gamification-based platforms in developing psychological hardiness, exploring four dimensions: commitment, control, challenge, and connection. In this study, a quasi-experimental approach was applied to two experimental groups. The first group used a gamification-based platform, while the second group used a regular platform without gamification. The study aimed to explore the effectiveness of gamification-based platforms in developing psychological hardiness among students with high levels of psychological disorders. Therefore, the study was conducted with a total of 46 eligible students detained in the Jeddah correctional facility. The study discussed the results and statistical tests used to examine the effect of gamification on psychological hardiness across its four dimensions. Several limitations and challenges that may have influenced the study's findings were also discussed, highlighting the need for further research. The results confirmed the effectiveness of using the gamification strategy in enhancing psychological hardiness by developing a sense of commitment, challenge, and control.